2019
DOI: 10.12691/wjce-7-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Organic Electronics - Part II: Quick & Easy Synthesis of the (Semi-)Conductive Polymer PEDOT: PSS in a Snap-Cap Vial

Abstract: Organic Electronics is an interdisciplinary and cutting-edge research field leading to innovative applications and products like ultra-thin and high-efficient organic LED displays, lightweight and transparent organic solar cells or printed organic field-effect transistors (to name only few). The core functional materials in such devices are organic (semi-)conductors like conjugated polymers, oligomers or small molecules. As a sequel to our former contribution in the World Journal of Chemical Education (Vol 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Here, the thiophene groups of PEDOT are electropolymerized with sulfonic acid groups of PSS. 35 37 We found that the polymerization process took few cycles to reach the oxidation less state.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Here, the thiophene groups of PEDOT are electropolymerized with sulfonic acid groups of PSS. 35 37 We found that the polymerization process took few cycles to reach the oxidation less state.…”
Section: Resultsmentioning
confidence: 90%
“…GCE/PEDOT:PSS was dipped into 0.01 mol/L PBS (at a pH level of 4.0) solution containing 100 μM FURO, and electropolymerization was performed by CV with a potential range of −0.2 to 0.8 V for three cycles with a scan rate of 100 mV s –1 as shown in Figure A. Here, the thiophene groups of PEDOT are electropolymerized with sulfonic acid groups of PSS. We found that the polymerization process took few cycles to reach the oxidation less state.…”
Section: Resultsmentioning
confidence: 99%
“…14) Beispiele mit starkem Bezug auf fachwissenschaftlich aktuelle Forschung sind die Weiterentwicklungen bei intrinsisch leitfähigen Polymeren, etwa Polypyrrol, 15) oder die Synthese eines halbleitenden Polymers für Oled. 16) Die Betrachtung des Photo-Blue-Bottle-Experiments über 25 Jahre zeigt exemplarisch die langfristige Entwicklung einer curricularen Innovation. 17) Weiterentwicklungen gab es zudem bei den Redoxflusssystemen für den Schulunterricht.…”
Section: Arbeiten In Deutschsprachigen Zeitschriftenunclassified
“…For the assembly of OLED devices, the concept of multilayers created by a technique called spin-coating have been used [8][9][10][11] . Spin-coating is widely used to create thin films, not only for OLED devices, but also for organic photovoltaic cell (OPV) devices [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%